Early Personal Quranic Manuscripts in Light of the Sana’a Palimpsest (DAM 01-27.1): An Analytical and Foundational Study - Adel Ibrahim Abushaar (مجلة كلية الشريعة والدراسات الإسلامية)
Objectives: This research focuses on the issue of the methodology of engaging with personal Quranic manuscripts (muṣḥafs) attributed to the early centuries of Islam. Based on a thorough examination of the Sana’a Palimpsest DAM 01-27.1, this study rebuts the Orientalist assertion that the Quran read by Muslims today has evolved from a lost, original text. This study is structured into three sections and seeks to fulfill three main objectives. First, to establish and clarify the relationship between orthography books (rasm) and the documentation of Quranic manuscripts, and to examine how these books define the orthographical features of the text. Second, to examine how Islamic sources addressed private muṣḥafs and provided rulings on them. Third, to provide an examination of the Sana’a Palimpsest.